Sistema de abastecimiento de agua mediante procesos de filtración, ablandamiento y desinfección para zonas rurales de Manabí, Ecuador. - Mendoza Cevallos, María Gabriela (2018)
Since the beginning of human civilization, man has established himself near water sources due to the availability of a certain quantity to drink and domestic use, however, these facts do not imply that the source has sufficient capacity or is of good quality. Safe, accessible and adequately treated water supplies are basic needs and essential components of primary health care, since they reduce diseases that mainly affect rural populations. Considering that, a water supply system was designed and built with filtration, softening and disinfection processes for rural areas, analyzing the water collection points at ESPAM MFL "El Limón" site, being compared with Table 2 of Maximum Permissible Limits (LMP) waters for human consumption and use that required conventional treatment of Book VI of the Unified Text of Environmental Secondary Legislation (TULSMA), in which the turbidity of well water, hardness and total coliforms exceeded the LMP, likewise, turbidity and total coliforms in river water. Finally, the water treated by the system was compared with the potable water requirements of the INEN 1108 Ecuadorian Technical Standard, which resulted in a 91.45% well water removal efficiency and 76.47% in river water, investment of $ 809.71 USD and maintenance of $100 USD per year for 5 years, being effective and object of implementation in other Manabí rural areas to meet the current demand.